Teori Evolusi Charles Darwin Perspektif Al-Qur’an - Ridwan, Rahmad; Rifandi, Abdul Juki; Damanik, Sri Murniati (Universitas Islam Negeri Sumatera Utara, 2023)
This paper will analyze the theory of human evolution that developed in the West and the theory of human evolution explained in the Qur'an with an interpretive approach. The method used in this writing is to use qualitative methods sourced from sharing books related to the above problems. The approach to the method of interpretation of the Qur'an uses thematic methods, because this method can examine contemporary problems. The theory of evolution began to be studied and debated in the 6th century BC, Diwali by the Greek philosophers Anaximander, Empedocles, Lucretius, the same opinion was also expressed by the Arab biologist Al Jahiz, the Persian philosopher Ibn Miskawaih, the Ikhwan As-Shafa, and the Chinese philosopher Zhuangzi. Furthermore, the theory of evolution was published by an English scientist named Charles Darwin, the results of his research on evolution, especially human evolution, explained that the theory of evolution was not created by God but stood alone. This opinion caused debate among scientists and religionists, especially Islam, rejected because it contradicted the Qur'an.